Association of Pelvic Trauma With Rates of Cesarean Section, Sexual Dysfunction, and Genitourinary Dysfunction in a National Database. (10th April 2023) - Chen, Kevin; Bhattacharjee, Sarah; Seidel, Henry; Dillman, Daryl B.; Strelzow, Jason A.
Abstract : Introduction: Pelvic fractures are severe injuries that can drastically affect a woman's quality of life through sexual dysfunction (SD), genitourinary dysfunction (GD), and increasing the potential need for future cesarean section (C-section). Limited research has captured long-term outcomes after pelvic fractures in women of childbearing age. This study aimed to determine the association between pelvic fractures and rates of C-section, SD, and GD. Methods: All women of childbearing age who sustained a pelvic fracture were identified in a national insurance database. A comparison group of patients with lower extremity long-bone fractures was selected. Patients who gave birth after injury were additionally identified. A minimum of 5 years of follow-up was required for inclusion. Rates of C-section, SD, and GD were compared between cohorts. Multivariate logistic regression analysis was conducted with the inclusion of diabetes, tobacco, hypertension, obesity, and advanced maternal age. Results: A total of 6, 174 patients with pelvic fracture and 27, 154 control fracture patients were identified. 434 patients with pelvic fracture (7.0%) and 1, 258 control fracture patients (4.6%) gave birth after fracture. Patients with pelvic fracture had a significantly higher rate of C-section (50.0% versus 38.8%, P < 0.001), SD diagnosis (10.9% versus 8.8%, P < 0.001), and urinary retention diagnosis (3.5% versus 2.8%, P < 0.001). No significant difference in global GD diagnosis was identified. Multivariate analyses showed that pelvic fracture was associated with C-section (odds ratio [OR]: 1.78; 95% confidence interval [95% CI]: 1.42 to 2.23, P < 0.001), SD diagnosis (OR: 1.23; 95% CI: 1.12 to 1.35, P < 0.001), and urinary retention diagnosis (OR: 1.35; 95% CI: 1.15 to 1.57, P < 0.001). Discussion: Pelvic fractures confer an intrinsic level of risk of C-section, SD, and urinary retention that is elevated beyond what would be expected from a traumatic lower extremity injury alone. Treating orthopaedic surgeons should actively counsel women regarding increased risks, openly discuss postinjury sequelae, and coordinate interspecialty care beyond initial treatment of acute trauma.